All for One and One for All? – Examining Convergent Validity and Responsiveness of the German Versions of the Tinnitus Questionnaire (TQ), Tinnitus Handicap Inventory (THI), and Tinnitus Functional Index (TFI) - Boecking, Benjamin; Brueggemann, Petra; Kleinjung, Tobias; Mazurek, Birgit (Frontiers in Psychology, 2021)
Abstract Background: Measurements of tinnitus-related distress and treatment responsiveness are key in understanding, conceptualizing and addressing this often-disabling symptom. Whilst several self-report measures exist, the heterogeneity of patient populations, available translations and treatment contexts requires ongoing psychometric replication and validation efforts. Objective: To investigate the convergent validity and responsiveness of the German versions of the Tinnitus Questionnaire [TQ], Tinnitus Handicap Inventory [THI] and Tinnitus Functional Index [TFI] in a large German-speaking sample of patients with chronic tinnitus who completed a psychologically anchored seven-day Intensive Multimodal Treatment Programme. Methods: Two-hundred-and-ten patients with chronic tinnitus completed all three questionnaires at baseline and post-treatment. Intra-class correlation coefficients determined the convergent validity of each questionnaire’s total and subscale scores. Treatment responsiveness was investigated by [a] comparing treatment-related change in responders vs. non-responders as classified by each questionnaire’s minimal clinically important difference-threshold, and [b] comparing agreement between the questionnaires’ responder classifications. Results: The total scores of all three questionnaires showed high agreement before and after therapy (TQ|THI: 0.80 [Pre], 0.83 [Post], TQ|TFI: 0.72 [Pre], 0.78 [Post], THI|TFI: 0.76 [Pre] 0.80 [Post]). All total scores changed significantly with treatment yielding small effect sizes. The TQ and TFI yielded comparable (19.65% and 18.64%) and the THI higher responder rates (38.15%). The TQ|THI and TQ|TFI showed fair, and the THI|TFI moderate agreement of responder classifications. Independent of classification, responders showed significantly higher change rates than non-responders across most scores. Each questionnaire’s total change score distinguished between responders and non-responders as classified using the remaining two questionnaires. Conclusion: The total scores of all three questionnaires show high convergent validity and thus, comparability across clinical and research contexts. By contrast, subscale scores show high inconsistency. Whilst the TFI appears well suited for research purposes, the THI may be better suited to measure psychological aspects of tinnitus-related distress and their changes with respectively focused treatment approaches.